CHARACTERIZATION OF PHYSICAL ACTIVITIES PERFORMED BY ADOLESCENTS FROM CURITIBA, BRAZIL - Silva,Alexandre Augusto de Paula da (2019)
ABSTRACT Introduction Various studies have been developed and published in relation to the recommendations for physical activity and associated factors. However, there is a lack of studies that detail the places where physical activity is practiced, as well as its frequency, duration and volume. Objective To describe the places, types, frequency, duration and volume of physical activities performed by adolescents in Curitiba, Brazil. Methods A cross-sectional study conducted in 2013-2014, through a household survey with 495 adolescents (12 to 17 years). The places used, and the frequencies of the practice of physical activity were self-reported as either “goes” or “does not go.” The practice of physical activity was determined through the Physical Activity Questionnaire for Adolescents, by type, frequency, duration and weekly volume. The types of physical activity were described with frequency distribution, weekly frequency, duration, and volume, by the median and interquartile range. Gender comparison was tested with the Chi-square and Mann-Whitney U tests (p<0.05). Results The most frequently reported places for physical activity were public squares, parks, soccer fields, schools and sports halls. Soccer fields, schools, sports halls and skate parks were more used by boys, while girls attended gyms (p<0.05). The physical activities most practiced were soccer, skating/rollerblading, cycling, walking and active games. A higher proportion of boys practiced soccer, skating/rollerblading, cycling, running/jogging, and basketball (p<0.05), whereas the physical activities most practiced by girls were walking, walking the dog, dancing, playing games, and gyms (p<0.05). Sports (720 min/week), aerobic exercises (400 min/week) and conditioning exercises (345 min/week) were the activities with the highest weekly volume. Boys showed higher weekly frequency, duration and volume of practice of sports and active games than girls (p<0.05). Conclusion Public places with structures were the most used places, and sports were the most practiced activities. Level of Evidence III; Study of nonconsecutive patients; without consistently applied ‘‘gold’’ reference standard.